The Effectiveness of Interactive Learning Media Based on Augmented Reality in Enhancing Elementary School Students’ Learning Motivation - Faisal Faisal; Rachmat Rachmat; Siti Nur Asia; Suherwin Suherwin; Abdul Ibrahim (Journal of Tecnologia Quantica, 2025)
This study aims to analyze the effectiveness of using augmented reality (AR) based learning media in enhancing the learning motivation of elementary school students. By employing a multiple linear regression approach on simulated data, this research evaluates the influence of several key factors, namely AR visualization quality, teacher support, ease of use, and supporting infrastructure. The analysis results show that AR visualization quality, teacher support, and ease of use significantly affect the improvement of learning motivation. The developed model has a coefficient of determination (R² ? 0.77), indicating that 77% of the variation in learning motivation can be explained by the independent variables, with a relatively small prediction error (RMSE ? 0.53). The F-test also confirmed that the model is overall significant. These findings indicate that the integration of AR in learning not only increases visual appeal but also strengthens the role of teachers and enhances students’ ease of interaction with the material. Nevertheless, this study is still based on simulated data, so further research with broader and more realistic empirical data is required to validate the results.